Measurement of Maximum Strain of Steel Beam Structures Based on Average Strains from Vibrating Wire Strain Gages. Issue 2 (14th April 2011) - Lee, H.M.; Park, H.S.
<x xml:space="preserve">Abstract</x> In structural health monitoring, the safety of steel beam structures can be assessed by comparing the measured maximum stress and the allowable stress of the beam calculated by a design code. For the case of a steel beam subjected to variable lateral loadings, many difficulties exist in measuring the maximum stress in a beam with point sensors that can measure the strain only at a local point of a beam since the location and magnitude of the maximum stress induced in a beam by the loading change. Although traditional strain sensors can measure the strain only at a local point, a vibrating wire strain gage (VWSG) that measures integrated strains over its gage length can consider the variation of strains due to variable loadings. This paper presents an estimation model to determine the maximum strains or stresses in a steel beam based on average strains measured using VWSGs. The model is derived by defining the relation between the average strains measured using VWSGs and the maximum strains of beams. The model is experimentally tested by comparing the maximum strain directly obtained from electrical strain gages and the estimated maximum strain based on the average strain from VWSGs.